Diabetes and sleep disturbances: findings from the Sleep Heart Health Study. - Resnick, Helaine E; Redline, Susan; Shahar, Eyal; Gilpin, Adele; Newman, Anne; Walter, Robert; Ewy, Gordon A; Howard, Barbara V; Punjabi, Naresh M (Diabetes Care, 2003)
OBJECTIVE: To test the hypothesis that diabetes is independently associated with sleep-disordered breathing (SDB), and in particular that diabetes is associated with sleep abnormalities of a central, rather than obstructive, nature. RESEARCH DESIGN AND METHODS: Using baseline data from the Sleep Heart Health Study (SHHS), we related diabetes to 1). the respiratory disturbance index (RDI; number of apneas plus hypopneas per h of sleep); 2). obstructive apnea index (OAI; >or=3 apneas/h of sleep associated with obstruction of the upper airway); 3). percent of sleep time < 90% O(2) saturation; 4). central apnea index (CAI; >or=3 apneas [without respiratory effort]/h sleep); 5). occurrence of a periodic breathing (Cheyne Stokes) pattern; and 6) sleep stages. Initial analyses excluding persons with prevalent cardiovascular disease (CVD) were repeated including these participants. RESULTS: Of the 5874 participants included in this report, 692 (11.8%) reported diabetes or were taking oral hypoglycemic medications or insulin and 1002 had prevalent CVD. Among the 4872 persons without CVD, 470 (9.6%) had diabetes. Diabetic participants had worse CVD risk factor profiles than their nondiabetic counterparts, including higher BMI, waist and neck circumferences, triglycerides, higher prevalence of hypertension, and lower HDL cholesterol (P < 0.001, all). Descriptive analyses indicated differences between diabetic and nondiabetic participants in RDI, sleep stages, sleep time <90% O(2) saturation, CAI, and periodic breathing (P < 0.05, all). However, multivariable regression analyses that adjusted for age, sex, BMI, race, and neck circumference eliminated these differences for all sleep measures except percent time in rapid eye movement (REM) sleep (19.0% among diabetic vs. 20.1% among nondiabetic subjects, P < 0.001) and prevalence of periodic breathing (odds ratio [OR] for diabetic subjects versus nondiabetic subjects 1.80, 95% CI 1.02-3.15). Additionally, adjusted analyses showed diabetes was associated with nonstatistically significant elevations in the odds of an increased central breathing index (OR 1.42, 95% CI 0.80-2.55). Addition to the analysis of the 1002 persons with prevalent CVD (including 222 people with diabetes) did not materially change these results. CONCLUSIONS: These data suggest that diabetes is associated with periodic breathing, a respiratory abnormality associated with abnormalities in the central control of ventilation. Some sleep disturbances may result from diabetes through the deleterious effects of diabetes on central control of respiration. The high prevalence of SDB in diabetes, although largely explained by obesity and other confounders, suggests the presence of a potentially treatable risk factor for CVD in the diabetic population.
Keywords: Aged; Diabetes Mellitus; Female; Humans; Logistic Models; Male; Middle Aged; Multivariate Analysis; Prevalence; Risk Factors; Sleep Apnea Syndromes; Sleep Apnea, Obstructive

Sleep and sleep-disordered breathing in adults with predominantly mild obstructive airway disease. - Sanders, Mark H; Newman, Anne B; Haggerty, Catherine L; Redline, Susan; Lebowitz, Michael; Samet, Jonathan; O'Connor, George T; Punjabi, Naresh M; Shahar, Eyal (Am J Respir Crit Care Med, 2003)
Neither the association between obstructive airways disease (OAD) and sleep apnea-hypopnea (SAH) nor the sleep consequences of each disorder alone and together have been characterized in an adult community setting. Our primary aims were (1) to determine if there is an association between OAD and SAH and (2) identify predictors of oxyhemoglobin desaturation during sleep in persons having OAD with and without SAH. Polysomnography and spirometry results from 5,954 participants in the Sleep Heart Health Study were analyzed. OAD was defined by a FEV1/FVC value less than 70%. Assessment of SAH prevalence in OAD was performed using thresholds of respiratory disturbance index (RDI) greater than 10 and greater than 15. A total of 1,132 participants had OAD that was predominantly mild (FEV1/FVC 63.81 +/- 6.56%, mean +/- SD). SAH was not more prevalent in participants with OAD than in those without OAD (22.32 versus 28.86%, with and without OAD, respectively, at RDI threshold values greater than 10; and 13.97 versus 18.63%, with and without OAD, respectively, at RDI threshold value greater than 15). In the absence of SAH, the adjusted odds ratio for sleep desaturation (> 5% total sleep time with saturation < 90%) was greater than 1.9 when FEV1/FVC was less than 65%. Participants with both OAD and SAH had greater sleep perturbation and desaturation than those with one disorder. Generally mild OAD alone was associated with minimally altered sleep quality. We conclude that (1) there is no association between generally mild OAD and SAH; (2) exclusive of SAH and after adjusting for demographic factors and awake oxyhemoglobin saturation, an FEV1/FVC value less than 65% is associated with increased risk of sleep desaturation; (3) desaturation is greater in persons with both OAD and SAH compared with each of these alone; and (4) individuals with generally mild OAD and without SAH in the community have minimally perturbed sleep.
Keywords: Aged; Cohort Studies; Female; Forced Expiratory Volume; Humans; Male; Middle Aged; Oxyhemoglobins; Polysomnography; Prospective Studies; Pulmonary Disease, Chronic Obstructive; Sleep; Sleep Apnea, Obstructive; Spirometry; Vital Capacity

Sleep-disordered breathing, glucose intolerance, and insulin resistance: the Sleep Heart Health Study. - Punjabi, Naresh M; Shahar, Eyal; Redline, Susan; Gottlieb, Daniel J; Givelber, Rachel; Resnick, Helaine E (Am J Epidemiol, 2004)
Clinic-based studies suggest that sleep-disordered breathing (SDB) is associated with glucose intolerance and insulin resistance. However, in the available studies, researchers have not rigorously controlled for confounding variables to assess the independent relation between SDB and impaired glucose metabolism. The objective of this study was to determine whether SDB was associated with glucose intolerance and insulin resistance among community-dwelling subjects (n=2,656) participating in the Sleep Heart Health Study (1994-1999). SDB was characterized with the respiratory disturbance index and measurements of oxygen saturation during sleep. Fasting and 2-hour glucose levels measured during an oral glucose tolerance test were used to assess glycemic status. Relative to subjects with a respiratory disturbance index of less than 5.0 events/hour (the reference category), subjects with mild SDB (5.0-14.9 events/hour) and moderate to severe SDB (> or =15 events/hour) had adjusted odds ratios of 1.27 (95% confidence interval: 0.98, 1.64) and 1.46 (95% confidence interval: 1.09, 1.97), respectively, for fasting glucose intolerance (p for trend < 0.01). Sleep-related hypoxemia was also associated with glucose intolerance independently of age, gender, body mass index, and waist circumference. The results of this study suggest that SDB is independently associated with glucose intolerance and insulin resistance and may lead to type 2 diabetes mellitus.
Keywords: Aged; Blood Gas Analysis; Body Constitution; Body Mass Index; Cohort Studies; Confounding Factors, Epidemiologic; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Fasting; Female; Glucose Intolerance; Glucose Tolerance Test; Humans; Insulin Resistance; Linear Models; Male; Middle Aged; Multivariate Analysis; Oxyhemoglobins; Polysomnography; Research Design; Risk Factors; Severity of Illness Index; Sleep Apnea Syndromes

Association of sleep time with diabetes mellitus and impaired glucose tolerance. - Gottlieb, Daniel J; Punjabi, Naresh M; Newman, Ann B; Resnick, Helaine E; Redline, Susan; Baldwin, Carol M; Nieto, F Javier (Arch Intern Med, 2005)
BACKGROUND: Experimental sleep restriction causes impaired glucose tolerance (IGT); however, little is known about the metabolic effects of habitual sleep restriction. We assessed the cross-sectional relation of usual sleep time to diabetes mellitus (DM) and IGT among participants in the Sleep Heart Health Study, a community-based prospective study of the cardiovascular consequences of sleep-disordered breathing. METHODS: Participants were 722 men and 764 women, aged 53 to 93 years. Usual sleep time was obtained by standardized questionnaire. Diabetes mellitus was defined as a serum glucose level of 126 mg/dL or more (> or =7.0 mmol/L) fasting or 200 mg/dL or more (> or =11.1 mmol/L) 2 hours following standard oral glucose challenge or medication use for DM. Impaired glucose tolerance was defined as a 2-hour postchallenge glucose level of 140 mg/dL or more (> or =7.8 mmol/L) and less than 200 mg/dL. The relation of sleep time to DM and IGT was examined using categorical logistic regression with adjustment for age, sex, race, body habitus, and apnea-hypopnea index. RESULTS: The median sleep time was 7 hours per night, with 27.1% of subjects sleeping 6 hours or less per night. Compared with those sleeping 7 to 8 hours per night, subjects sleeping 5 hours or less and 6 hours per night had adjusted odds ratios for DM of 2.51 (95% confidence interval, 1.57-4.02) and 1.66 (95% confidence interval, 1.15-2.39), respectively. Adjusted odds ratios for IGT were 1.33 (95% confidence interval, 0.83-2.15) and 1.58 (95% confidence interval, 1.15-2.18), respectively. Subjects sleeping 9 hours or more per night also had increased odds ratios for DM and IGT. These associations persisted when subjects with insomnia symptoms were excluded. CONCLUSIONS: A sleep duration of 6 hours or less or 9 hours or more is associated with increased prevalence of DM and IGT. Because this effect was present in subjects without insomnia, voluntary sleep restriction may contribute to the large public health burden of DM.
Keywords: Age Factors; Aged; Aged, 80 and over; Blood Glucose; Diabetes Mellitus; Disease Progression; Female; Glucose Intolerance; Humans; Male; Middle Aged; Odds Ratio; Prevalence; Prospective Studies; Sleep; Surveys and Questionnaires; Time Factors; United States

Association of usual sleep duration with hypertension: the Sleep Heart Health Study. - Gottlieb, Daniel J; Redline, Susan; Nieto, F Javier; Baldwin, Carol M; Newman, Anne B; Resnick, Helaine E; Punjabi, Naresh M (Sleep, 2006)
STUDY OBJECTIVES: Limited experimental data suggest that sleep restriction acutely elevates blood pressure; however, little is known about the relationship between usual sleep duration and hypertension. This study assesses the relationship between usual sleep duration and hypertension in a community-based cohort. DESIGN: Cross-sectional observational study. SETTING: The Sleep Heart Health Study, a community-based prospective study of the cardiovascular consequences of sleep-disordered breathing. PARTICIPANTS: Two thousand eight hundred thirteen men and 3097 women, aged 40 to 100 years. INTERVENTIONS: None. MEASUREMENTS AND RESULTS: Usual weekday and weekend sleep durations were obtained by questionnaire, and their weighted average were categorized as less than 6, 6 to less than 7, 7 to less than 8, 8 to less than 9, and 9 or more hours per night. Hypertension was defined as a systolic blood pressure of 140 mm Hg or greater, a diastolic blood pressure of 90 mm Hg or greater, or use of medication to treat hypertension. The relationship between sleep duration and hypertension was examined using categorical logistic regression with adjustment for age, sex, race, apnea-hypopnea index, and body mass index. Compared to subjects sleeping 7 to less than 8 hours per night, those sleeping less than 6 and between 6 and 7 hours per night had adjusted odds ratios for hypertension of 1.66 (95% confidence interval 1.35-2.04) and 1.19 (1.02-1.39), respectively, whereas those sleeping between 8 and 9 and 9 or more hours per night had adjusted odds ratios for hypertension of 1.19 (1.04-1.37) and 1.30 (1.04-1.62), respectively (p < .0001 for association of sleep duration with hypertension). These associations persisted when analyses were further adjusted for caffeine and alcohol consumption, current smoking, insomnia symptoms, depression symptoms, sleep efficiency, and prevalent diabetes mellitus or cardiovascular disease. CONCLUSIONS: Usual sleep duration above or below the median of 7 to less than 8 hours per night is associated with an increased prevalence of hypertension, particularly at the extreme of less than 6 hours per night.
Keywords: Adult; Aged; Aged, 80 and over; Body Mass Index; Cohort Studies; Comorbidity; Cross-Sectional Studies; Female; Health Surveys; Humans; Hypertension; Male; Middle Aged; Odds Ratio; Prospective Studies; Sleep; Sleep Apnea, Obstructive; Sleep Deprivation; Statistics as Topic

Cigarette smoking and nocturnal sleep architecture. - Zhang, Lin; Samet, Jonathan; Caffo, Brian; Punjabi, Naresh M (Am J Epidemiol, 2006)
Cigarette smoking has been associated with a high prevalence of sleep-related complaints. However, its effects on sleep architecture have not been fully examined. The primary objective of this investigation was to assess the impact of cigarette smoking on sleep architecture. Polysomnography was used to characterize sleep architecture among 6,400 participants of the Sleep Heart Health Study (United States, 1994-1999). Sleep parameters included total sleep time, latency to sleep onset, sleep efficiency, and percentage of time in each sleep stage. The study sample consisted of 2,916 never smokers, 2,705 former smokers, and 779 current smokers. Compared with never smokers, current smokers had a longer initial sleep latency (5.4 minutes, 95% confidence interval (CI): 2.9, 7.9) and less total sleep time (14.0 minutes, 95% CI: 6.4, 21.7). Furthermore, relative to never smokers, current smokers also had more stage 1 sleep (relative proportion = 1.24, 95% CI: 1.14, 1.33) and less slow wave sleep (relative proportion = 0.86, 95% CI: 0.78, 0.95). Finally, no differences in sleep architecture were noted between former and never smokers. The results of this study show that cigarette smoking is independently associated with disturbances in sleep architecture, including a longer latency to sleep onset and a shift toward lighter stages of sleep. Nicotine in cigarette smoke and acute withdrawal from it may contribute to disturbances in sleep architecture.
Keywords: Aged; Arousal; Chi-Square Distribution; Female; Humans; Male; Middle Aged; Polysomnography; Prevalence; Regression Analysis; Risk Factors; Sleep Stages; Sleep Wake Disorders; Smoking; United States

Fasting glycemia in sleep disordered breathing: lowering the threshold on oxyhemoglobin desaturation. - Stamatakis, Katherine; Sanders, Mark H; Caffo, Brian; Resnick, Helaine E; Gottlieb, Dan J; Mehra, Reena; Punjabi, Naresh M (Sleep, 2008)
STUDY OBJECTIVES: Commonly used definitions of sleep-disordered breathing (SDB) are based on identifying discrete events of breathing abnormalities during sleep that are accompanied by an oxyhemoglobin desaturation (delta SaO2) of at least 4%. However, it is not known whether disordered breathing events with oxyhemoglobin desaturation less than 4% are associated with clinical sequelae such as abnormalities in fasting glycemia. DESIGN: Cross-sectional study. SUBJECTS AND SETTING: Participants from the Sleep Heart Health Study (SHHS) with a fasting glucose measurement made within a year of the baseline polysomnogram. MEASUREMENTS AND RESULTS: SDB severity was defined using the apnea-hypopnea index (AHI) and the hypopnea index (HI) by counting events with different levels of oxyhemoglobin desaturation (0.0%-1.9%, 2.0%-2.9%, 3.0%-3.9%, > or = 4.0%). Fasting glucose levels were used to classify individuals into normal (<100 mg/dL), impaired (100-125 mg/dL), and diabetic (> or = 126 mg/dL) groups. Ordinal logistic regression was used to determine the adjusted relative odds of an abnormal glucose value across quartiles of the hypopnea index, independent of factors such as age, body mass index, waist circumference, and usual sleep duration. The prevalence of impaired and diabetic fasting glucose in the analytical sample was 32.9% and 5.8%, respectively. The covariate-adjusted relative odds of impaired or diabetic fasting glucose in the highest versus the lowest AHI quartile was 1.35 (95% CI: 1.04-1.76) for events with a delta SaO2 > or = 4.0%, 1.72 (95% CI: 1.20-2.48) for events with a delta SaO2 between 3.0%-3.9%, 1.41 (95% CI: 1.07-1.86) for events with a delta SaO2 between 2.0%-2.9%, and 1.07 (95% CI: 0.84-1.37) for events with a delta SaO2 between 0.0%-1.9%. The corresponding odds ratios for the HI were 1.47 (95% CI: 1.13-1.92), 2.25 (95% CI: 1.59-3.19), 1.44 (95% CI: 1.09-1.90), and 1.15 (95% CI: 0.90-1.47), respectively. CONCLUSIONS: The results of this study indicate that SDB events accompanied by oxyhemoglobin desaturation of between 2% to 4% are associated with fasting hyperglycemia. These findings suggest that milder degrees of SDB may predispose to adverse metabolic outcomes.
Keywords: Aged; Blood Glucose; Body Mass Index; Cohort Studies; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Fasting; Female; Humans; Male; Middle Aged; Odds Ratio; Oxygen; Oxyhemoglobins; Polysomnography; Reference Values; Sleep Apnea, Obstructive

Relation of sleep-disordered breathing to carotid plaque and intima-media thickness. - Wattanakit, Keattiyoat; Boland, Lori; Punjabi, Naresh M; Shahar, Eyal (Atherosclerosis, 2008)
BACKGROUND: Sleep-disordered breathing (SDB) is associated with clinical cardiovascular disease (CVD), but its relation to subclinical atherosclerosis remains to be determined. METHODS: We analyzed the cross-sectional associations of SDB, measured by the respiratory disturbance index (RDI), a hypoxemia index, and an arousal index, with carotid plaque and carotid intima-media thickness (IMT), measured by ultrasound. The sample included 985 participants in the Sleep Heart Health Study (mean age-62, median RDI-8.7) with no history of coronary heart disease and stroke, of whom 396 had evidence of a carotid plaque. RESULTS: As compared with the first quartile of the RDI (0-1.2), the crude odds ratio for carotid plaque was 1.14, 1.27, and 1.48 for the second (1.3-4.1), third (4.2-10.7), and fourth (>10.7) quartile, respectively. After adjustment for CVD risk factors, the corresponding odds ratios were reduced (1.00, 1.04, 1.07, and 1.25). Similarly, the unadjusted mean carotid IMT increased with RDI, but adjusted means (mm) were similar (0.84, 0.85, 0.84, 0.85). Spline regression models did not show monotonicity of the dose-response functions at the right end of the RDI distribution. Neither the hypoxemia index nor the arousal index was associated with carotid plaque or carotid IMT. CONCLUSION: The results of this study suggest that crude, positive associations between SDB and subclinical atherosclerosis can be attributed to confounding by CVD risk factors.
Keywords: Aged; Carotid Arteries; Carotid Artery Diseases; Female; Humans; Male; Middle Aged; Odds Ratio; Risk Factors; Sleep Apnea Syndromes; Tunica Intima; Tunica Media; Ultrasonography

Sleep-disordered breathing and cardiovascular disease: an outcome-based definition of hypopneas. - Punjabi, Naresh M; Newman, Anne B; Young, Terry B; Resnick, Helaine E; Sanders, Mark H (Am J Respir Crit Care Med, 2008)
RATIONALE: Epidemiologic studies on the consequences of sleep-disordered breathing invariably use the apnea-hypopnea index as the primary measure of disease severity. Although hypopneas constitute a majority of disordered breathing events, significant controversy remains about the best criteria used to define these events. OBJECTIVES: The current investigation sought to assess the most appropriate definition for hypopneas that would be best correlated with cardiovascular disease. METHODS: A community sample of middle-aged and older adults was recruited as part of the Sleep Heart Health Study. Full-montage polysomnography was conducted and hypopneas were defined using different thresholds of oxyhemoglobin desaturation with and without arousals. Prevalent cardiovascular disease was assessed based on self-report. Logistic regression analysis was used to characterize the independent association between the hypopnea index and prevalent cardiovascular disease. MEASUREMENTS AND MAIN RESULTS: Using a sample of 6,106 adults with complete data on cardiovascular disease status and polysomnography, the current study found that hypopneas associated with an oxyhemoglobin desaturation of 4% or more were associated with prevalent cardiovascular disease independent of confounding covariates. The adjusted prevalent odds ratios for quartiles of the hypopnea index using a 4% desaturation criterion were as follows: 1.00 (<1.10 events/h), 1.10 (1.01-3.20 events/h), 1.33 (3.21-7.69 events/h), and 1.41 (>7.69 events/h). Hypopnea measures based on less than 4% oxyhemoglobin desaturation or presence of arousals showed no association with cardiovascular disease. CONCLUSIONS: Hypopneas comprise a significant component of sleep-disordered breathing in the general community. By varying the criteria for defining hypopneas, this study demonstrates that hypopneas with a desaturation of at least 4% are independently associated with cardiovascular disease. In contrast, no association was observed between cardiovascular disease and hypopneas associated with milder desaturations or arousals.
Keywords: Aged; Apnea; Cardiovascular Diseases; Cohort Studies; Female; Humans; Male; Middle Aged; Odds Ratio; Oxyhemoglobins; Polysomnography; Sleep Apnea Syndromes; Terminology as Topic

Sleep-disordered breathing and impaired glucose metabolism in normal-weight and overweight/obese individuals: the Sleep Heart Health Study. - Seicean, Sinziana; Kirchner, H Lester; Gottlieb, Daniel J; Punjabi, Naresh M; Resnick, Helaine; Sanders, Mark; Budhiraja, Rohit; Singer, Mendel; Redline, Susan (Diabetes Care, 2008)
OBJECTIVE: To characterize the association between sleep-disordered breathing (SDB) and impaired fasting glucose (IFG), impaired glucose tolerance (IGT), combined IFG and IGT, and occult diabetes in individuals of different body habitus. RESEARCH DESIGN AND METHODS: Cross-sectional analysis of 2,588 participants (aged 52-96 years; 46% men) without known diabetes. SDB was defined as respiratory disturbance index >or=10 events/h. IFG, IGT, occult diabetes, and body weight were classified according to recent accepted guidelines. Participants with and without SDB were compared on prevalence and odds ratios for measures of impaired glucose metabolism (IGM), adjusting for age, sex, race, BMI, and waist circumference. RESULTS: SDB was observed in 209 nonoverweight and 1,036 overweight/obese participants. SDB groups had significantly higher adjusted prevalence and adjusted odds of IFG, IFG plus IGT, and occult diabetes. The adjusted odds ratio for all subjects was 1.3 (95% CI 1.1-1.6) for IFG, 1.2 (1.0-1.4) for IGT, 1.4 (1.1-2.7) for IFG plus IGT, and 1.7 (1.1-2.7) for occult diabetes. CONCLUSIONS: SDB was associated with occult diabetes, IFG, and IFG plus IGT, after adjusting for age, sex, race, BMI, and waist circumference. The magnitude of these associations was similar in nonoverweight and overweight participants. The consistency of associations across all measures of IGM and body habitus groups and the significant association between SDB and IFG plus IGT, a risk factor for rapid progression to diabetes, cardiovascular disease, and mortality, suggests the importance of SDB as a risk factor for clinically important levels of metabolic dysfunction.
Keywords: Aged; Aged, 80 and over; Body Weight; Cardiovascular Diseases; Cross-Sectional Studies; Female; Glucose Intolerance; Glucose Tolerance Test; Humans; Male; Middle Aged; Obesity; Overweight; Polysomnography; Reference Values; Sleep Wake Disorders

Subjective and objective sleep quality in patients on conventional thrice-weekly hemodialysis: comparison with matched controls from the sleep heart health study. - Unruh, Mark L; Sanders, Mark H; Redline, Susan; Piraino, Beth M; Umans, Jason G; Chami, Hassan; Budhiraja, Rohit; Punjabi, Naresh M; Buysse, Daniel; Newman, Anne B (Am J Kidney Dis, 2008)
BACKGROUND: Studies examining sleep in the hemodialysis (HD) population have largely lacked an adequate comparison group. It therefore is uncertain whether poor sleep quality in the HD population reflects age, chronic health conditions, or effects of conventional HD therapy. STUDY DESIGN: Cross-sectional matched-group study. SETTING & PARTICIPANTS: Forty-six in-center HD patients were compared with 137 community participants participating in the Sleep Heart Health Study matched for age, sex, body mass index, and race. PREDICTOR: HD patients compared with community-dwelling non-HD participants. OUTCOMES & MEASUREMENTS: Home unattended polysomnography was performed and scored by using similar protocols. Sleep habits and sleepiness were assessed by using the Sleep Habits Questionnaire and Epworth Sleepiness Scale. RESULTS: Average age of study samples was 63 years, 72% were white, and average body mass index was 28 +/- 5 kg/m(2). HD patients were significantly more likely than community participants to have short sleep (odds ratio, 3.27; 95% confidence interval, 1.16 to 9.25) and decreased sleep efficiency (odds ratio, 5.5; 95% confidence interval, 1.5 to 19.6). HD patients reported more difficulty getting back to sleep (odds ratio, 2.25; 95% confidence interval, 1.11 to 4.60) and waking up too early (odds ratio, 2.39; 95% confidence interval, 1.01 to 5.66). There was no association between polysomnography sleep time and self-reported sleep time (r = 0.09; P = 0.6) or between the Epworth Sleepiness Scale and severity of sleep apnea (r = 0.10; P = 0.5) in the HD population. LIMITATIONS: The study was limited to participants older than 45 years. CONCLUSIONS: Kidney failure treated with thrice-weekly HD is significantly associated with poor subjective and objective sleep quality.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Cross-Sectional Studies; Disease Progression; Female; Follow-Up Studies; Heart Rate; Humans; Incidence; Kidney Failure, Chronic; Male; Middle Aged; Odds Ratio; Pennsylvania; Polysomnography; Prognosis; Renal Dialysis; Retrospective Studies; Risk Factors; Severity of Illness Index; Sleep; Sleep Apnea Syndromes; Surveys and Questionnaires

Sleep-disordered breathing and mortality: a prospective cohort study. - Punjabi, Naresh M; Caffo, Brian S; Goodwin, James L; Gottlieb, Daniel J; Newman, Anne B; O'Connor, George T; Rapoport, David M; Redline, Susan; Resnick, Helaine E; Robbins, John A; Shahar, Eyal; Unruh, Mark L; et al. (PLoS Med, 2009)
BACKGROUND: Sleep-disordered breathing is a common condition associated with adverse health outcomes including hypertension and cardiovascular disease. The overall objective of this study was to determine whether sleep-disordered breathing and its sequelae of intermittent hypoxemia and recurrent arousals are associated with mortality in a community sample of adults aged 40 years or older. METHODS AND FINDINGS: We prospectively examined whether sleep-disordered breathing was associated with an increased risk of death from any cause in 6,441 men and women participating in the Sleep Heart Health Study. Sleep-disordered breathing was assessed with the apnea-hypopnea index (AHI) based on an in-home polysomnogram. Survival analysis and proportional hazards regression models were used to calculate hazard ratios for mortality after adjusting for age, sex, race, smoking status, body mass index, and prevalent medical conditions. The average follow-up period for the cohort was 8.2 y during which 1,047 participants (587 men and 460 women) died. Compared to those without sleep-disordered breathing (AHI: <5 events/h), the fully adjusted hazard ratios for all-cause mortality in those with mild (AHI: 5.0-14.9 events/h), moderate (AHI: 15.0-29.9 events/h), and severe (AHI: >or=30.0 events/h) sleep-disordered breathing were 0.93 (95% CI: 0.80-1.08), 1.17 (95% CI: 0.97-1.42), and 1.46 (95% CI: 1.14-1.86), respectively. Stratified analyses by sex and age showed that the increased risk of death associated with severe sleep-disordered breathing was statistically significant in men aged 40-70 y (hazard ratio: 2.09; 95% CI: 1.31-3.33). Measures of sleep-related intermittent hypoxemia, but not sleep fragmentation, were independently associated with all-cause mortality. Coronary artery disease-related mortality associated with sleep-disordered breathing showed a pattern of association similar to all-cause mortality. CONCLUSIONS: Sleep-disordered breathing is associated with all-cause mortality and specifically that due to coronary artery disease, particularly in men aged 40-70 y with severe sleep-disordered breathing. Please see later in the article for the Editors' Summary.
Keywords: Aged; Coronary Artery Disease; Female; Humans; Hypoxia; Male; Middle Aged; Odds Ratio; Proportional Hazards Models; Prospective Studies; Risk Factors; Sex Factors; Sleep Apnea Syndromes; Survival Analysis

A novel approach to prediction of mild obstructive sleep disordered breathing in a population-based sample: the Sleep Heart Health Study. - Caffo, Brian; Diener-West, Marie; Punjabi, Naresh M; Samet, Jonathan (Sleep, 2010)
This manuscript considers a data-mining approach for the prediction of mild obstructive sleep disordered breathing, defined as an elevated respiratory disturbance index (RDI), in 5,530 participants in a community-based study, the Sleep Heart Health Study. The prediction algorithm was built using modern ensemble learning algorithms, boosting in specific, which allowed for assessing potential high-dimensional interactions between predictor variables or classifiers. To evaluate the performance of the algorithm, the data were split into training and validation sets for varying thresholds for predicting the probability of a high RDI (≥7 events per hour in the given results). Based on a moderate classification threshold from the boosting algorithm, the estimated post-test odds of a high RDI were 2.20 times higher than the pre-test odds given a positive test, while the corresponding post-test odds were decreased by 52% given a negative test (sensitivity and specificity of 0.66 and 0.70, respectively). In rank order, the following variables had the largest impact on prediction performance: neck circumference, body mass index, age, snoring frequency, waist circumference, and snoring loudness.
Keywords: Age Factors; Aged; Algorithms; Body Mass Index; Cohort Studies; Female; Humans; Male; Middle Aged; Predictive Value of Tests; Risk Factors; ROC Curve; Sleep Apnea Syndromes; Snoring; Waist Circumference

Obstructive sleep apnea-hypopnea and incident stroke: the sleep heart health study. - Redline, Susan; Yenokyan, Gayane; Gottlieb, Daniel J; Shahar, Eyal; O'Connor, George T; Resnick, Helaine E; Diener-West, Marie; Sanders, Mark H; Wolf, Philip A; Geraghty, Estella M; Ali, Tauqeer; Lebowitz, Michael; et al. (Am J Respir Crit Care Med, 2010)
RATIONALE: Although obstructive sleep apnea is associated with physiological perturbations that increase risk of hypertension and are proatherogenic, it is uncertain whether sleep apnea is associated with increased stroke risk in the general population. OBJECTIVES: To quantify the incidence of ischemic stroke with sleep apnea in a community-based sample of men and women across a wide range of sleep apnea. METHODS: Baseline polysomnography was performed between 1995 and 1998 in a longitudinal cohort study. The primary exposure was the obstructive apnea-hypopnea index (OAHI) and outcome was incident ischemic stroke. MEASUREMENTS AND MAIN RESULTS: A total of 5,422 participants without a history of stroke at the baseline examination and untreated for sleep apnea were followed for a median of 8.7 years. One hundred ninety-three ischemic strokes were observed. In covariate-adjusted Cox proportional hazard models, a significant positive association between ischemic stroke and OAHI was observed in men (P value for linear trend: P = 0.016). Men in the highest OAHI quartile (>19) had an adjusted hazard ratio of 2.86 (95% confidence interval, 1.1-7.4). In the mild to moderate range (OAHI, 5-25), each one-unit increase in OAHI in men was estimated to increase stroke risk by 6% (95% confidence interval, 2-10%). In women, stroke was not significantly associated with OAHI quartiles, but increased risk was observed at an OAHI greater than 25. CONCLUSIONS: The strong adjusted association between ischemic stroke and OAHI in community-dwelling men with mild to moderate sleep apnea suggests that this is an appropriate target for future stroke prevention trials.
Keywords: Aged; Female; Humans; Longitudinal Studies; Male; Middle Aged; Polysomnography; Proportional Hazards Models; Prospective Studies; Severity of Illness Index; Sex Factors; Sleep Apnea, Obstructive; Stroke

Prospective study of obstructive sleep apnea and incident coronary heart disease and heart failure: the sleep heart health study. - Gottlieb, Daniel J; Yenokyan, Gayane; Newman, Anne B; O'Connor, George T; Punjabi, Naresh M; Quan, Stuart F; Redline, Susan; Resnick, Helaine E; Tong, Elisa K; Diener-West, Marie; Shahar, Eyal (Circulation, 2010)
BACKGROUND: Clinic-based observational studies in men have reported that obstructive sleep apnea is associated with an increased incidence of coronary heart disease. The objective of this study was to assess the relation of obstructive sleep apnea to incident coronary heart disease and heart failure in a general community sample of adult men and women. METHODS AND RESULTS: A total of 1927 men and 2495 women > or =40 years of age and free of coronary heart disease and heart failure at the time of baseline polysomnography were followed up for a median of 8.7 years in this prospective longitudinal epidemiological study. After adjustment for multiple risk factors, obstructive sleep apnea was a significant predictor of incident coronary heart disease (myocardial infarction, revascularization procedure, or coronary heart disease death) only in men < or =70 years of age (adjusted hazard ratio 1.10 [95% confidence interval 1.00 to 1.21] per 10-unit increase in apnea-hypopnea index [AHI]) but not in older men or in women of any age. Among men 40 to 70 years old, those with AHI > or =30 were 68% more likely to develop coronary heart disease than those with AHI <5. Obstructive sleep apnea predicted incident heart failure in men but not in women (adjusted hazard ratio 1.13 [95% confidence interval 1.02 to 1.26] per 10-unit increase in AHI). Men with AHI > or =30 were 58% more likely to develop heart failure than those with AHI <5. CONCLUSIONS: Obstructive sleep apnea is associated with an increased risk of incident heart failure in community-dwelling middle-aged and older men; its association with incident coronary heart disease in this sample is equivocal.
Keywords: Adult; Aged; Coronary Disease; Female; Heart Failure; Humans; Longitudinal Studies; Male; Middle Aged; Polysomnography; Proportional Hazards Models; Prospective Studies; Sleep Apnea, Obstructive; Survival Analysis

Sleepiness, quality of life, and sleep maintenance in REM versus non-REM sleep-disordered breathing. - Chami, Hassan A; Baldwin, Carol M; Silverman, Angela; Zhang, Ying; Rapoport, David; Punjabi, Naresh M; Gottlieb, Daniel J (Am J Respir Crit Care Med, 2010)
RATIONALE: The impact of REM-predominant sleep-disordered breathing (SDB) on sleepiness, quality of life (QOL), and sleep maintenance is uncertain. OBJECTIVE: To evaluate the association of SDB during REM sleep with daytime sleepiness, health-related QOL, and difficulty maintaining sleep, in comparison to their association with SDB during non-REM sleep in a community-based cohort. METHODS: Cross-sectional analysis of 5,649 Sleep Heart Health Study participants (mean age 62.5 [SD = 10.9], 52.6% women, 22.6% ethnic minorities). SDB during REM and non-REM sleep was quantified using polysomnographically derived apnea-hypopnea index in REM (AHI(REM)) and non-REM (AHI(NREM)) sleep. Sleepiness, sleep maintenance, and QOL were respectively quantified using the Epworth Sleepiness Scale (ESS), the Sleep Heart Health Study Sleep Habit Questionnaire, and the physical and mental composites scales of the Medical Outcomes Study Short Form (SF)-36. MEASUREMENTS AND MAIN RESULTS: AHI(REM) was not associated with the ESS scores or the physical and mental components scales scores of the SF-36 after adjusting for demographics, body mass index, and AHI(NREM) x AHI(REM) was not associated with frequent difficulty maintaining sleep or early awakening from sleep. AHI(NREM) was associated with the ESS score (beta = 0.25; 95% confidence interval [CI], 0.16 to 0.34) and the physical (beta = -0.12; 95% CI, -0.42 to -0.01) and mental (beta = -0.20; 95% CI, -0.20 to -0.01) components scores of the SF-36 adjusting for demographics, body mass index, and AHI(REM). CONCLUSIONS: In a community-based sample of middle-aged and older adults, REM-predominant SDB is not independently associated with daytime sleepiness, impaired health-related QOL, or self-reported sleep disruption.
Keywords: Aged; Disorders of Excessive Somnolence; Female; Humans; Male; Middle Aged; Polysomnography; Quality of Life; Sleep; Sleep Apnea Syndromes; Sleep, REM

Utility of sleep stage transitions in assessing sleep continuity. - Laffan, Alison; Caffo, Brian; Swihart, Bruce J; Punjabi, Naresh M (Sleep, 2010)
STUDY OBJECTIVES: Sleep continuity is commonly assessed with polysomnographic measures such as sleep efficiency, sleep stage percentages, and the arousal index. The aim of this study was to examine whether the transition rate between different sleep stages could be used as an index of sleep continuity to predict self-reported sleep quality independent of other commonly used metrics. DESIGN AND SETTING: Analysis of the Sleep Heart Health Study polysomnographic data. PARTICIPANTS: A community cohort. MEASUREMENTS AND RESULTS: Sleep recordings on 5,684 participants were deemed to be of sufficient quality to allow visual scoring of NREM and REM sleep. For each participant, we tabulated the frequency of transitions between wake, NREM sleep, and REM sleep. An overall transition rate was determined as the number of all transitions per hour sleep. Stage-specific transition rates between wake, NREM sleep, and REM sleep were also determined. A 5-point Likert scale was used to assess the subjective experience of restless and light sleep the morning after the sleep study. Multivariable regression models showed that a high overall sleep stage transition rate was associated with restless and light sleep independent of several covariates including total sleep time, percentages of sleep stages, wake time after sleep onset, and the arousal index. Compared to the lowest quartile of the overall transition rate (<7.76 events/h), the odds ratios for restless sleep were 1.27, 1.42, and 1.38, for the second (7.77-10.10 events/h), third (10.11-13.34 events/h), and fourth (≥13.35 events/h) quartiles, respectively. Analysis of stage-specific transition rates showed that transitions between wake and NREM sleep were also independently associated with restless and light sleep. CONCLUSIONS: Assessing overall and stage-specific transition rates provides a complementary approach for assessing sleep continuity. Incorporating such measures, along with conventional metrics, could yield useful insights into the significance of sleep continuity for clinical outcomes.
Keywords: Age Factors; Aged; Arousal; Body Mass Index; Cohort Studies; Female; Humans; Male; Middle Aged; Polysomnography; Predictive Value of Tests; Risk Factors; Sex Factors; Sleep Stages; Sleep Wake Disorders

Sleep-disordered breathing and caffeine consumption: results of a community-based study. - Aurora, R Nisha; Crainiceanu, Ciprian; Caffo, Brian; Punjabi, Naresh M (Chest, 2012)
BACKGROUND: Sleepiness is one of the most burdensome symptoms of sleep-disordered breathing (SDB). While caffeine is frequently used to avert sleepiness, the association between SDB and caffeine use has not been thoroughly explored. The current study examined whether SDB is associated with caffeine consumption and if factors such as sex, age, and daytime sleepiness explain or modify the association. METHODS: Data from the Sleep Heart Health Study, a community-based study on the consequences of SDB, were used to characterize the association between SDB and caffeine intake. SDB was assessed with full-montage polysomnography. Caffeine use was quantified as the number of cans of soda or the cups of coffee or tea consumed daily. The Epworth Sleepiness Scale was used to assess daytime sleepiness. Multivariable negative binomial regression models were used to characterize the independent association between SDB and caffeine use. RESULTS: Caffeinated soda, but not tea or coffee, intake was independently associated with SDB severity. Compared with participants without SDB, the relative ratios for caffeinated soda consumption in women with mild, moderate, and severe SDB were 1.20 (CI, 1.03-1.41), 1.46 (CI, 1.14-1.87), and 1.73 (CI, 1.23-2.42), respectively. For men, an association was only noted with severe SDB and caffeinated soda use. Age did not modify the SDB-caffeine association, and sleepiness could not explain the observed associations. CONCLUSIONS: SDB is independently associated with caffeinated soda use in the general community. Identifying excessive caffeine used in SDB has potential significance given the cardiovascular effects of caffeine and untreated SDB.
Keywords: Age Factors; Aged; Caffeine; Carbonated Beverages; Coffee; Data Collection; Drinking Behavior; Female; Humans; Male; Middle Aged; Polysomnography; Prevalence; Retrospective Studies; Sex Factors; Sleep Apnea Syndromes; Tea